Anti-rubella seroprevalence assessment in an adult sample population in Italy - Bechini, Angela; Zanella, Beatrice; Bonito, Benedetta; Betti, Marta; Stancanelli, Enrica; Del Riccio, Marco; Salvati, Cristina; Bonanni, Paolo; Bianchi, Jacopo; Biondi, Ilaria; Chellini, Martina; Innocenti, Maddalena; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. Despite global immunization efforts, rubella remains a public health concern, particularly in high- and middleincome countries. This study focused on rubella seroprevalence in the province of Florence, Italy, aiming to identify susceptibility clusters, especially among women in their childbearing age.Methods. A cross-sectional study was conducted between April 2018 and December 2019, enrolling 430 adult subjects (age over 18 years). Serum samples were collected, and anti-rubella antibodies were quantified using the ELISA test. Data were analyzed descriptively and compared by sex, nationality, and age groups using statistical tests.Results. The overall rubella seroprevalence was high (92.3%), with no significant differences between genders or nationalities. Among childbearing-age females (18-49 years), the highest seroprevalence was observed in the 30-39 age group (94.1%). However, susceptibility clusters exceeding the 5% threshold set by WHO were identified, especially in females aged 40-49 years (7.0%). Conclusions. Despite high overall seroprevalence, the study identified pockets of susceptibility, even in childbearing age women. Continuous monitoring, targeted immunization strategies, and public health interventions are recommended to maintain rubella elimination, emphasizing the importance of sustained vaccination efforts to protect vulnerable populations.